Sobre a recepção de O Antigo Regime e a Revolução pela historiografia da Revolução Francesa: da publicação da obra ao contexto do Bicentenário de 1789 - José Miguel Nanni Soares (Araucaria)
The purpose of this paper is to offer an overview –although summary– of The Old Regime and the Revolution by the historiography of the French Revolution, from its publication to the context of the Bicentennial celebration (1789-1989).Among other aspects, it was demonstrated how, in spite of relevant and favorable opinions from eminent historians and literary critics, the famous Tocqueville work faced serious editorial and ideological challenges in the period between June 1856 and the first centenary of its appearance.In the wake of the postwar changes of the 1950s and, to a large extent, due to the important contributions of the eminent republican and socialist historian Georges Lefebvre, Tocqueville’s historical work began to attract a growing consideration of academic historians and the general public, becoming a pivotal author in both historiography and contemporary political debate during and after the celebration of the Bicentenary of the Revolution of 1789.